Vimentin Protein In Situ Expression Predicts Less Tumor Metastasis and Overall Better Survival of Endometrial Carcinoma. (14th March 2022) - Zhang, Xuefang; Cao, Guangming; Diao, Xiaoli; Bai, Wenyu; Zhang, Yang; Wang, Shuzhen
Abstract : Background . Vimentin, a cytoplasmic intermediate filament protein, has been recently identified to be a prognostic biomarker in some cancers. However, the function of vimentin in endometrial carcinoma (EC) remains unclear. Our study aimed at evaluating vimentin expression in EC and preliminarily exploring the role of vimentin in EC progression. Methods . In total, 341 EC patients who underwent surgical follow-up were enrolled in the retrospective study. Vimentin expression levels in EC tissues were analyzed using immunohistochemistry. Furthermore, the vimentin (VIM) gene expression levels in 547 samples in The Cancer Genome Atlas (TCGA) were analyzed. To examine the prognostic value of vimentin in EC, Kaplan-Meier survival analysis was performed, and a Cox model was established. Gene set enrichment analysis (GSEA) was also conducted using the Kyoto Encyclopedia of Genes and Genomes (KEGG) database to explore the role of vimentin in EC progression. Results . Negative vimentin expression in EC correlated significantly with lymph node metastasis, deep myometrium invasion (MI), lymph vascular space invasion (LVSI), advanced Federation International of Gynecology and Obstetrics Association (FIGO) stages (III and IV), and high tumor grade. Vimentin negativity was more common in type 2 EC than that in type 1 EC, and vimentin-negative patients had poorer overall survival compared with vimentin-positive patients. The results of GSEA suggested that vimentin may interact with classical pathways in EC. Conclusions . Negative vimentin expression correlates with tumor metastasis and worse overall survival in EC, suggesting that it may be an excellent prognostic biomarker for this disease. The mechanism by which vimentin contributes to EC progression needs to be explored in the future.